Disorders in Hepatic Copper Secretion: Wilson's Disease and Pleomorphic Syndromes - Lalioti, Vasiliki; Tsubota, Akihito; Sandoval, Ignacio V. (Seminars in Liver Disease, 2017)
Wilson's disease (WD) is a rare disease the prevalence of which is higher than previously thought. Caused by genetic variations that target the copper (Cu) transporting P-ATPase Atp7b and disrupt the elimination of Cu by the liver, Atp7b truncations are associated with early severe liver disease and missense mutations with the late presentation of neurologic disorders. The asymptomatic initiation and false unimportance of initial symptoms often delays the crucial early diagnosis and a treatment that is lifesaving. The occasional acute liver failure persistently threatens the life of patients with WD. The gravity and progression of the disease are strongly dependent on the genetic background that organizes the response to the oxidative damage produced by the raised levels of free Cu. In this review, the authors focus on the prevalence, genetics, pathogenesis, clinical presentation, and treatment options in WD. They also discuss the new association of cuprotoxicosis with pleomorphic syndromes, of which MEDNIK is the first example, produced by genetic variations that disrupt the universal mechanisms of protein transport and thus perturb the traffic of Atp7b linked to Cu excretion.
Keywords: liver; copper; Atp7b; toxicosis